Green Marketing and Service Quality as Determinants of Consumer Loyalty in Coffee Shop Businesses in Semarang - Abdullah; Edwin Zusrony; Myra Andriana; Wesly Tumbur ML Tobing (ITB AAS Indonesia Surakarta, 2026)
The purpose of this study is to evaluate the relationship between green marketing and service quality regarding consumer loyalty. This study uses a quantitative method approach. In this study the primary data is used and disseminated directly to the respondents using a Likert scale of 1 to 5 points. The research population is all consumers who have made purchases at 5 coffee shops with the age range of 18-35 and live in the City of Semarang. The sampling used is non-random sampling utilizing purposeful sampling approach. The total number of participants is 70 respondents. The data analysis approach used is the multiple linear regression method and the study data processing used is SmartPLS 4.1.1.8 software. The results of the study indicate that service quality has a positive and significant effect on consumer loyalty and green marketing has no significant direct effect. However, concurrently these variables have a favorable and significant effect on consumer loyalty of coffee shop business in Semarang. The benefits of this study for coffee shop enterprises include as a consideration in building effective marketing strategies, especially through the improvement of service quality and optimization of green marketing in an effort to increase client loyalty.